Biomass-based palm shell activated carbon and palm shell carbon molecular sieve as gas separation adsorbents. Issue 4 (April 2015) - Sethupathi, Sumathi; Bashir, Mohammed JK; Akbar, Zinatizadeh Ali; Mohamed, Abdul Rahman
Lignocellulosic biomass has been widely recognised as a potential low-cost source for the production of high added value materials and proved to be a good precursor for the production of activated carbons. One of such valuable biomasses used for the production of activated carbons is palm shell. Palm shell ( endocarp ) is an abundant by-product produced from the palm oil industries throughout tropical countries. Palm shell activated carbon and palm shell carbon molecular sieve has been widely applied in various environmental pollution control technologies, mainly owing to its high adsorption performance, well-developed porosity and low cost, leading to potential applications in gas-phase separation using adsorption processes. This mini-review represents a comprehensive overview of the palm shell activated carbon and palm shell carbon molecular sieve preparation method, physicochemical properties and feasibility of palm shell activated carbon and palm shell carbon molecular sieve in gas separation processes. Some of the limitations are outlined and suggestions for future improvements are pointed out.